An experimental study on charring of cellulosic biomass in ultrasonic vibration-assisted pelleting. (6th January 2011) - Feng, Q.; Cong, W.L.; Zhang, M.; Pei, Z.J.; , C.Z. Ren
Cellulosic biofuels can be used as transportation fuels. But their manufacturing cost is high, partly because the low density of cellulosic feedstocks causes their transportation and handling costly. Ultrasonic Vibration-Assisted (UV-A) pelleting can increase the density of cellulosic feedstocks. However, charring of biomass sometimes happens during UV-A pelleting and may adversely affect the yield of biofuel conversion. This paper reports an experimental investigation on charring of cellulosic biomass in UV-A pelleting. It studies effects of moisture content of the biomass and pelleting variables. The results will be helpful when selecting pelleting conditions to avoid biomass charring.